Lady Windemere syndrome as the cause of chronic cough. A propos of one case - León Valdivies, Yusbiel José (2015)
Nontuberculous mycobacteria are rarely recognized in the world today; their prevalence is increasing due to suspicion in immunocompromised patients or in those suffering from chronic illnesses such as cystic fibrosis. A case with of Lady Windermere Syndrome diagnosis that originally started with chronic cough is presented. Tomography showed bilateral bronchiectasis in the left lingual segment and in the middle and lower right lobe. Mycobacterium avium-intracellulare complex was isolated using bronchoscopy. The lack of suspicion of nontuberculous mycobacteria in patients without risk factors and chronic cough leads to diagnosis delay and clinical deterioration of the patient.